2013
DOI: 10.1371/journal.pone.0073794
|View full text |Cite
|
Sign up to set email alerts
|

SNP (–617C>A) in ARE-Like Loci of the NRF2 Gene: A New Biomarker for Prognosis of Lung Adenocarcinoma in Japanese Non-Smoking Women

Abstract: PurposeThe transcription factor NRF2 plays a pivotal role in protecting normal cells from external toxic challenges and oxidative stress, whereas it can also endow cancer cells resistance to anticancer drugs. At present little information is available about the genetic polymorphisms of the NRF2 gene and their clinical relevance. We aimed to investigate the single nucleotide polymorphisms in the NRF2 gene as a prognostic biomarker in lung cancer.Experimental DesignWe prepared genomic DNA samples from 387 Japane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 51 publications
3
38
1
Order By: Relevance
“…At the level of gene expression, it is interesting that an allele of the SNP rs6721961 (2617C . A) located at the ARE enhancer of the human NRF2 gene abolished selfinduction of NRF2, and this correlated with remarkable survival of these cancer patients (Okano et al, 2013). Epigenetic changes due to promoter hypermethylation of three CpG sites of KEAP1 have been described in lung tumors, resulting in consequent NRF2 activation that could be reversed by 5-aza-29-deoxycitydine treatment .…”
Section: The Kelch-like Ech-associated Protein 1 Paradox In Cancermentioning
confidence: 90%
“…At the level of gene expression, it is interesting that an allele of the SNP rs6721961 (2617C . A) located at the ARE enhancer of the human NRF2 gene abolished selfinduction of NRF2, and this correlated with remarkable survival of these cancer patients (Okano et al, 2013). Epigenetic changes due to promoter hypermethylation of three CpG sites of KEAP1 have been described in lung tumors, resulting in consequent NRF2 activation that could be reversed by 5-aza-29-deoxycitydine treatment .…”
Section: The Kelch-like Ech-associated Protein 1 Paradox In Cancermentioning
confidence: 90%
“…A SNP (rs6721961, c.-617A) in human NRF2 gene has been found related to survival rate after chemotherapies. The homozygous alleles (c.-617C) were identified to increase the binding affinity of NRF2 to AREs by 2-3-fold in 55.8% of reported Japanese patients with primary lung cancer, and this may pose the aberrant transactivation of NRF2 gene and subsequent increased protein level of downstream genes (Okano et al, 2013). These data point that NRF2-dependent chemoresistance could be considered as a therapeutic strategy on the basis of rapid genotyping method for personalized cancer treatment.…”
Section: Lung Cancermentioning
confidence: 96%
“…The NRF2 gene polymorphisms is associated with oxidative stress-related and inflammation-related diseases, and also with some cancers (Marzec et al, 2007;Cordova et al, 2010;Bouligand et al, 2011;Hartikainen et al, 2012;Okano et al, 2013). However, the impact of NRF2 polymorphisms on CCA has not been studied to date.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphism of NRF2 on several SNPs (including rs6721961 and rs2886162) were associated with breast cancer risk (Hartikainen et al, 2012). Moreover, a recent report showed that rs6721961 polymorphism is associated with female lung cancer (Okano et al, 2013). The role of SNPs in NRF2 as the modifier of NRF2 function or as a biomarker for diseases is needed further clarification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation